Dampak Kebijakan PP Nomor 55 Tahun 2022, Kesadaran Wajib Pajak, Dan Kepercayaan Kepada Pemerintah Tehadap Kepatuhan Wajib Pajak UMKM - Kusufiyah, Yunita Valentina; Anggraini, Dina (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The government has made various efforts to increase MSME taxpayer compliance, this is because the high contribution of MSMEs to GDP (Gross Domestic Product) reaches 60.5 percent and can absorb 96.9 percent of the total national workforce (Hidranto, 2022) . One of the government's policies is to provide a reduction in tax rates for MSMEs by issuing Government Regulation No. 55 of 2022 concerning Adjustments to Income Tax Rules. This rule, especially in Chapter Taxpayer compliance does not come from external factors of the taxpayer but from the taxpayer's self, namely the taxpayer's awareness and trust in the government. This research aims to empirically test Government Regulation Policy No. 55 of 2022, Awareness and Trust in the government regarding taxpayer compliance. This research was conducted on individual MSME Taxpayers registered at KPP 1 and KPP 2 Padang.Using the Sovin formula provides a minimum sample size of 99.22 which is rounded up to 100 individual MSME taxpayers in Padang City. This research uses a data collection method by distributing questionnaires to respondents in the form of a list of questions prepared on paper and Google form. The results of this research prove that there is no influence of the policy of Order No. 55 of 2022 with a reduction in MSME income tax rates on MSME taxpayer compliance in Padang City, while the variables of awareness and trust in the government have an influence on MSME taxpayer compliance in Padang City.